Forensic Evidence As A Mean Of Proof In Developing Prima Facie Case In Takhbib Criminal Offence - Muhammad Hazim Ahmad; Ruqayyah Razak; Nurul Syahirah Saharudin; Syaril Nizam Omar; Ahmad Syukran Baharuddin; Hasnizam Hashim (UUM PRESS, 2024)
Indexed by SCOPUS/MYCITE